DEMOKRASI PENDIDIKAN DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - MUHAMMAD ROIHAN DAULAY (Fitrah: Jurnal Kajian Ilmu-Ilmu Keislaman, 2017)
Democracy has a set of value that becomes its characteristic to achieve the purpose of democracy itself. Through time to time, democracy has shown a significant progression and becomes a crucial topic not only in politic and economy but also in education. Democracy in education is kind of freedom that is used by the educator to develop the quality of education.  Islam has emphasized Islamic people to treat human in a good way and also the equality especially in education. All people have the same right and opportunity in education furthermore to build the consciousness of them to study without any discrimination in all aspect of life